Insinuation of Extrapolative Factors of Diagnostic Importance in Breast Cancer Patients Experiencing Thyroid Dysfunction - Samina Malik, Mahwish Arooj, Sulayman Waquar, Naveed Shuja, Arif Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Breast cancer (BC) is the most common malignancy in women and now regarded as the commonest cancer overall. Over 2 million new cases were diagnosed in 2018, accounting for almost 25% of cancer cases among women. The main objective of the study is to find the insinuation of extrapolative factors of diagnostic importance in breast cancer patients experiencing thyroid dysfunction. Materials and methods: This correlational study was conducted on Jinnah Hospital patients with the permission of ethical committee of the hospital and consent of the patients. The data was collected from 88 cases and 50 controls. All the patients who had a definite diagnosis of BC along with, hyperthyroidism, hypothyroidism, autoimmune thyroid disease (AITD), or thyroid cancer were included in this study. The study population was divided into three comparative groups: (1) controls (n = 50), (2) BC cases with hypothyroidism (n = 27), and (3) BC cases with hyperthyroidism (n = 61). Results: The mean age was 47.325±4.59 years for controls, 51.59±8.59 years for the hypothyroid cases, and 50.59±5.58 years for the hyperthyroid cases. The mean systolic blood pressure (SBP) for controls, hypothyroid and hyperthyroid was 121.25±6.58 mmHg, 98.259±8.59 mmHg and 129.65±7.59 mmHg respectively. The P-values less than 0.05 were considered to be significant (table 01). The demographic and hematological data of control, hypothyroid and hyperthyroid groups was tabulated. A positive correlation of breast cancer in women with hyperthyroidism and a slightly negative correlation in women with hypothyroidism was found. Conclusion: There appears to be an association between the thyroid function level and breast cancer risk. It can be extrapolated that anxiety associated with hyperthyroidism may play a role in stress induced BC. Therefore, thyroid function should be monitored in patients at risk of BC. Keyword: Breast cancer, Thyroid, Dysfunction, Hypothyroidism, Hyperthyroidism, Anxiety.